MINGGU ULIN: STRATEGI BELAJAR SAMBIL BERMAIN SEBAGAI METODE PENDIDIKAN KARAKTER DI SAKOLA MOTEKAR - Azzahra, Marsha Syaila; Trysiani, Nabila Ayu; Kurnia, Wanda; Yulianti, Dena; Rabbania, Nayla Zain; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The emergence of gadgets affects children's character if parents cannot manage their use. Therefore, activities are needed that accommodate children to continue to grow into good individuals. At the same time, in Ciamis Regency there is a community school called Sakola Motekar which carries out an ironwood week activity as an effort to instill character through playing while learning activities which are of course in accordance with efforts to instill character in children. In this activity we contributed as facilitators in the Ironwood Week activities. The methods used in this community service include observation, interviews, learning while playing. As a result of this activity which was carried out for 1 month with 4 meetings, we were able to create games that contain character education, such as: (1) Able to increase children's creativity, (2) Able to increase self-confidence and improve communication skills, (3) Increase empathy and build children's social life, as well as (4) Develop a sense of tolerance.